2011
DOI: 10.1007/978-94-007-2561-4_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in the Aging Processes of Yeast

Abstract: This chapter reviews the role of mitochondria and of mitochondrial metabolism in the aging processes of yeast and the existing evidence for the "mitochondrial theory of aging mitochondrial theory of aging ". Mitochondria are the major source of ATP in the eukaryotic cell but are also a major source of reactive oxygen species reactive oxygen species (ROS) and play an important role in the process of apoptosis and aging. We are discussing the mitochondrial theory of aging mitochondrial theory of aging (TOA), its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 120 publications
0
45
0
Order By: Relevance
“…The extension of CLS depends on the existence of an intact respiratory metabolism 38394041 and also by the expression of intact antioxidant defenses 424344. Given that these requirements are affected in cells expressing both Coq7-pAAA and Coq7-pDED, CLS have been measured in these cells (Figure 3A and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The extension of CLS depends on the existence of an intact respiratory metabolism 38394041 and also by the expression of intact antioxidant defenses 424344. Given that these requirements are affected in cells expressing both Coq7-pAAA and Coq7-pDED, CLS have been measured in these cells (Figure 3A and Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…1,26 To test whether mitochondria mediate D 2 O-promoted longevity, we conducted CLS assays on yeast strains with mitochondrial deficiency. The mip1Δ strain carries deletion of the gene encoding the sole yeast mitochondrial DNA polymerase gamma subunit 27 and are short-lived (39.4% reduction in mean CLS versus wild type, P <1E−10; Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…As mitochondria are the major source of reactive oxygen species, mtDNA may be vulnerable to oxidative damage (Harman, 1956). The mitochondrial genome has a higher mutation rate than the nuclear genome (Lynch et al ., 2008), and the biology of yeast mitochondria has been implicated in aging (Breitenbach et al ., 2012). We found that mtDNA was consistently lost in WT cells after they generated 10–20 daughter cells, and this effect was also seen in young cells after several aging cycles, making many of these cells respiration deficient (Fig 3…”
Section: Resultsmentioning
confidence: 99%